In defense of the imputation hearing. A proposal in the Colombian criminal procedure system (2020)
The formulation of charges in Law 906 of 2004 is the act through which the preliminary accusation made in the criminal process is communicated to the accused. Legislation, jurisprudence and doctrine have understood it as an act on the part of which no control is applied, ignoring the epistemological and ideological presuppositions of the accusatory criminal system. The legislator has found in this context a favorable environment to propose regulatory initiatives that advocate the elimination of the formulation of charges in Law 906 of 2004. This text maintains that the preliminary formulation of charges or imputation is a control to the Criminal claim from a procedural (formal), threats (material) and evidentiary perspective, without losing sight of the constitutional interest that the judge of control of guarantees must protect.Spani